Media Matters: A Critical Analysis of Black Panther’s Role in the Pursuit of Cultural and Racial Media Representation - Laurent, Geneviève (Université d'Ottawa | University of Ottawa, 2021)
This paper uses the 2018 film Black Panther as a framework for examining the intrinsic link between mass media representations of racial/ethnic minorities and societal perceptions towards these identity groups. A sample of 33 Canadians between the ages of 18 and 30 were surveyed to collect various opinions on the representations in Black Panther. Results were validated using a content analysis and were then analyzed through the lens of critical race theory, reception theory, and gaze theory. This set the stage for exploring how the representations of Black identity and ‘Africanicity’ in the film contributed to its commercial, critical, and cultural success in North America, as well as the ways in which these representations may have changed the perception of Black identities and Africanicity by Canadian young adults.